Corrigendum to: V. A. Sokolov, “On the Existence Problem of Finite Bases of Identities in the Algebras of Recursive Functions”, Modeling and analysis of information systems, vol. 27, no. 3, pp. 304-315, 2020. DOI: https://doi.org/10.18255/1818-1015-2020-3-304-315 - Valery Anatolyevich Sokolov (Моделирование и анализ информационных систем)
The author regrets that in the original list the references [3] and [4] are in the wrong places and they should be rearranged. In addition, [3] has the wrong article title. The corrected reference list is shown below.The author would like to apologize for an inconvenience caused.References[1] A. I. Mal'tsev, “Constructive algebras I”, Russian Mathematical Surveys, vol. 16, no. 3, pp. 77-129, 1961.[2] A. I. Mal'tsev, Algoritmy i rekursivnye funktsii. Moscow: Nauka, 1965, In Russian.[3] R. M. Robinson, “Primitive recursive functions”, Bulletin of the American Mathematical Society, vol. 53, no. 10,pp. 925-942, 1947.[4] J. Robinson, “General recursive functions”, Proceedings of the American Mathematical Society, vol. 1, no. 6,pp. 703-718, 1950.[5] V. A. Sokolov, “Ob odnom klasse tozhdestv v algebre Robinsona”, in 14-ya Vsesoyuznaya algebraicheskaya konferentsiya: tezisy dokladov, In Russian, vol. 2, Novosibirsk, 1977, pp. 123-124.[6] P. M. Cohn, Universal Algebra. New York, Evanston, and London: Harper & Row, 1965.[7] A. Robinson, “Equational logic for partial functions under Kleene equality: a complete and an incomplete set of rules”, The Journal of Symbolic Logic, vol. 54, no. 2, pp. 354-362, 1989.